Strategies for the Production of Molecular Animations - Werner, Erik (Frontiers in Bioinformatics, 2022)
Molecular animations play an increasing role in scientific visualisation and science communication. They engage viewers through non-fictional, documentary type storytelling and aim at advancing the audience. Every scene of a molecular animation is to be designed to secure clarity. To achieve this, knowledge on design principles from various design fields is essential. The relevant principles help to draw attention, guide the eye, establish relationships, convey dynamics and/or trigger a reaction. The tools of general graphic design are used to compose a signature frame, those of cinematic storytelling and user interface design to choreograph the relative movement of characters and cameras. Clarity in a scientific visualisation is reached by simplification and abstraction where the choice of the adequate representation is of great importance. A large set of illustration styles is available to chose the appropriate detail level but they are constrained by the availability of experimental data. For a high-quality molecular animation, data from different sources can be integrated, even filling the structural gaps to show a complete picture of the native biological situation . For maintaining scientific authenticity it is good practice to mark use of artistic licence which ensures transparency and accountability. The design of motion requires knowledge from molecule kinetics and kinematics. With biological macromolecules, four types of motion are most relevant: thermal motion, small and large conformational changes and Brownian motion. The principles of dynamic realism should be respected as well as the circumstances given in the crowded cellular environment. Ultimately, consistent complexity is proposed as overarching principle for the production of molecular animations and should be achieved between communication objective and abstraction/simplification, audience experience and scientific complexity, experiment and representation, characters and environment as well as structure and motion representation.